Fatal Sepsis Due to Stenotrophomonas Maltophilia in Stem Cell Recipient – Case Report - Stojanoski, Zlate (My University, 2011)
Background: Infections are frequent cause of further morbidity and mortality in stem cells recipients. Infection-related mortality is mainly due to severe bacterial sepsis, pneumonia and fungal infections. Case Report: We report a 60 years old patient with AML. In the complete remission he is received high-dose chemotherapy followed by autologous peripheral blood stem cell transplantation. The patient was treated in sterile room, conditioned with HEPA filters. Antibiotic prophylaxis regimen consisted Ciprofloxacin 1.0 gr/day, Itraconazol 400 mg/day, Acyclovir 1500 mg/day, and Immunoglobulins IV 0.1 mg/kg once per week. From day +5 patient became febrile (Ne<0.5 x 103/mL). First line antibiotic regimen consisted third-generation anti-pseudomonal cephalosporine and amynoglicoside during a 72 h, but with no response. As a second line antibiotic therapy was introduced Vancomicyn 2.0 gr/day. On day +10 from blood culture and urine culture was isolated Stenotrophomonas maltophillia with in vitro succeptibilities only to Ciprofloxacin (+3). Co-trimoxasole and again Ciprofloxacin in maximal doses was administered, but patient deteriorate, and in sepsis with signes of endotoxic shock he die on day +15. Conclusion: Despite use of broad-spectrum antibiotics as prophylaxis, Gram-negative bacteria are still potentially fatal for immunocompromised patients. Microbiological monitoring on local microflora is mandatory for all transplant centers and intensive care units.
Keywords: stem cell transplantation; infections